National Integration of Pakistan: An Assessment of Political Leadership of Huseyn Shaheed Suhrawardy - Rizwan Ullah Kokab; Mahboob Hussain (Journal of Political Studies, 2017)
Pakistan, during its first quarter, was in direct threat to disintegration. A Separatist Movement in eastern wing of Pakistan was in progress that ultimately ended with the bifurcation of Pakistan. There were very few leaders in Pakistan during the early phases of the secessionist movement who could foresee the danger to the integration of Pakistan and fewer of them had the capacity to appease that movement as well as belonged to the eastern wing. Huseyn Shaheed Suhrawardy was only one of the most prominent of such type. This paper is appraisal of his leadership capacities in curbing the disintegration of Pakistan. His awareness of the challenge of disintegration, his loyalty with the state of Pakistan, his position in the minds of Bengalis that could convince them to remain with Pakistan, his efforts for establishing the links between two wings, and obstacles in his way have been reviewed. It has also been examined how his rivals in politics wasted his utility for the integration of Pakistan.